Teachers' Motivation to Participate in Internal Audit as a Factor of Educational Quality - Liudmila Rupšienė; Vilija Targamadzė (Lithuanian Sports University, 2018)
In recent years a strategy of high quality education has been established in education policy, stimulating the adoption of transparent education quality assessment system, the basic component of which is internal / external audit. In practice, though, it is observed that teachers lack motivation to participate in internal audit activities, therefore, danger arises for implementation of strategic educational provision. That stimulated a research in 2006, aiming at revelation and analysis of motivating factors for teachers' participation within activities of internal audit. A quantitative design (survey) was chosen for the research. The sample was composed in two regions of the country by employing the method of cluster sampling. Altogether 589 teachers participated in the research. Quantitative data were analyzed by employing methods of factor and correlation analysis, Chi-square and Anova tests were chosen to identify differences. During the research, ﬁ ve factors that motivated teachers' participation in the internal audit activities were identiﬁ ed: 1) a wish to self-assess the situation of education in one's school; 2) the principal's demonstrated trust in teachers; 3) the opportunity of choice provided to the teachers; 4) the opportunity for self-expression provided to the teachers; and 5) ﬁ nancial incentives. The teachers with longer term of teaching experience were more motivated to participate in the internal audit activities by the trust demonstrated by the school principal than their less experienced colleagues. Fi- nancial incentives for the participation in the internal audit activities and the opportunity of choice tended to motivate women more than men. In the analysis of the teachers' attitudes to internal audit, three groups of attitudes were singled out: 1) internal audit was a meaningless and boring activity, imposed upon teachers, that did not improve the quality of the school performance; 2) internal audit meant extra work for teachers; and 3) internal audit was indispensable for the school performance, however, it had organizational shortcomings. The majority of the teachers tended to view internal audit as extra work (93%). During the research, we established an essential relationship between the negative view of internal audit and the direct motives of the participation in the internal audit activities: the direct motivation to participate in the internal audit of those teachers who took a negative view of the said audit was weaker. The more teachers participate in the activities of internal audit the stronger their negative attitude towards it becomes. Increase of this negative attitude may witness inadequate reward for the job performed. Teachers' expectations are mostly related to ﬁ nancial remuneration for participation in activities of internal audit - such expectations are typical of 1/3 of the respondents. On the other hand, our research also established the relationship between a negative view of internal audit and indirect motives of the participation in the internal audit activities. The teachers who took a negative view of internal audit less frequently tended to indicate that they were motivated to participate in the internal audit activities by the wish to deserve the principal's trust or the need for self-expression and choice. Another managerial problem as established in the research was the organizational dimension: 46% of the respondents stated that internal audit was indispensable, however, it had organizational shortcomings. Results of the research allow to conclude that teachers' motivation to participate in activities of internal audit is mostly related to the management of the process. Adequate remunaration and more efﬁ cient organization of internal audit as well as the management of the personnel (teachers) ought to improve teachers' motivation to participate in the activities of internal audit. Keywords: teachers' motivation, internal audit at school, educational quality.